Factors Influencing Employee Retention Among Production Operators in Manufacturing Companies In Malaysia - Tan, Pei Ling; Omar, Siti Sarah (Research in Management of Technology and Business, 2022)
Malaysia has effectively diversified its economy from agriculture and commodity-based to one that currently includes service and manufacturing industries since achieving independence in 1957. Furthermore, foreign direct investment generates new jobs and opportunities for local employees in Malaysia. Employees with relevant skills, knowledge, and talents have more options to determine their career path. In this study, four factors namely compensation, career development, work-life balance and work environment that may affect employees to make a decision about their career and may be important factors in employee retention for the organization. The main objective of this study is to identify the relationship between the employee retention with compensation, career development, work-life balance and work environment. The study examines if the above factors influencing the employee retention among the production operator in manufacturing company in Malaysia. The target population of this study was 415 local production operators in bricks manufacturing, biscuits manufacturing, furniture manufacturing, pallet manufacturing, fruits manufacturing and textile manufacturing. The questionnaires of study were self-administered, and a total of 192 production operators responded. The study concluded that work-life balance and work environment have a positive and significant impact on employee retention among production operators in manufacturing companies in Malaysia. Hence, it is essential for organizations to formulate and implement their retention strategies through a better work-life balance, and a better working environment.